2012
DOI: 10.2105/ajph.2011.300387
|View full text |Cite
|
Sign up to set email alerts
|

Joe Camel in a Bottle: Diageo, the Smirnoff Brand, and the Transformation of the Youth Alcohol Market

Abstract: I have documented the shift in youth alcoholic beverage preference from beer to distilled spirits between 2001 and 2009. I have assessed the role of distilled spirits industry marketing strategies to promote this shift using the Smirnoff brand marketing campaign as a case example. I conclude with a discussion of the similarities in corporate tactics across consumer products with adverse public health impacts, the importance of studying corporate marketing and public relations practices, and the implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…In this context, it is important to consider the historic and strategic convergence of the soda pop and alcohol markets over time as they target the youth market in an attempt to build brand loyalty at an early age. [57][58][59] From a public health perspective, placing alcohol products in grocery stores also increases community exposure to end-of-aisle, point-of-purchase, and entryway displays of liquor products that have been found to be effective mechanisms to increase alcohol purchases. 60 …”
Section: Alcohol Reforms and Proximity To Outletsmentioning
confidence: 99%
“…In this context, it is important to consider the historic and strategic convergence of the soda pop and alcohol markets over time as they target the youth market in an attempt to build brand loyalty at an early age. [57][58][59] From a public health perspective, placing alcohol products in grocery stores also increases community exposure to end-of-aisle, point-of-purchase, and entryway displays of liquor products that have been found to be effective mechanisms to increase alcohol purchases. 60 …”
Section: Alcohol Reforms and Proximity To Outletsmentioning
confidence: 99%
“…Among the factors contributing to the harms, alcohol marketing to young people is seen as an important issue (Austin and Rich 2001;Babor et al 2010;Casswell and Zhang 1998;Center on Alcohol Marketing and Youth 2008;Gordon, Hastings, Moodie 2010;McCreanor et al 2008;Mosher 2012;Smith and Foxcroft 2009). Babor and colleagues reviewed the international evidence on the role of marketing and concluded that despite the complexities of establishing causality … 'alcohol advertising increases the likelihood that young people will start to use alcohol and will drink more if they are already using alcohol' (Babor et al 2010, 189).…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2011 European School Survey Project on Alcohol and Other Drugs (ESPAD) report, spirits are the second most popular beverage type, after beer, among young people in Europe [5]. This is in line with findings pointing to the ever-increasing advertising of distilled spirits in the United States [6,7], and the view that distilled spirits companies have played a role in increasing consumption of spirits by young people [7,8]. Given the association between spirits consumption and binge drinking [9] and the adverse effects of consumption of spirits relative to other beverage types [8] among young people, this finding is a major public health concern.…”
mentioning
confidence: 60%